Response of stock market volatility to foreign equity investments - Kalu O. Emenike; Christian Ugwueze Amu (Journal of Contemporary Economic and Business Issues, 2019)
This study evaluates the response of stock market volatility to foreign equity investments. Specifically, the study examines how foreign portfolio investment and foreign direct equity investment influence stock market volatility in Nigeria, using monthly data from January 2007 to July 2017. Results of preliminary analyses of stock market returns series show evidence of negative skewness, leptokurtosis, non-normal distribution, and average positive monthly return. Estimates from the GARCH-X (1,1) model show evidence of volatility clustering in the stock market returns. The estimates also show that stock market volatility responds to changes in foreign portfolio investment. On the other hand, changes in foreign direct equity investment do not influence stock market volatility. The key implication is for investors to adjust their portfolio to changes in the foreign portfolio investment, in order to mitigate stock market volatility, and for stock market regulators to encourage more inflow of foreign direct equity investment as a more stable source of foreign equity investment.
Keywords: G11; G32; F21; 330; equity investment; stock market volatility; foreign direct equity investment; foreign portfolio investment